Microwave-assisted green synthesis, characterization, and in vitro antibacterial activity of NiO nanoparticles obtained from lemon peel extract - Heng Mei Hsuan; Win Yip Foo; Cheah Eddy Seong Guan; Chan Yu Bin; Rahman Md. Khalilur; Sultana Sabiha; Tey Lai-Hock; Wong Ling Shing; Djearamane Sinouvassane; Akhtaruzzaman Md.; Aminuzzaman Mohammod (Green Processing and Synthesis)
In the realm of nanotechnology, the synthesis of nanoparticles using environmentally benign methods, such as using plant extracts, has garnered significant attention. This work reports a simple and eco-friendly approach for the synthesis of nickel oxide nanoparticles (NiO NPs) utilizing microwave irradiation in the presence of lemon peel extract as a green reducing agent and Ni(CH3COO)2·2H2O as a precursor. Numerous analytical techniques were employed to determine the optical, morphological, and structural properties of the green-synthesized NiO NPs. The findings revealed that the resulting NiO NPs are pure, with an average size of 34 nm and a spherical geometry, possessing a face-centered-cubic crystalline structure. The antibacterial activities of the NiO NPs were preliminarily investigated against Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) and Gram-negative bacteria (Klebsiella pneumoniae and Salmonella typhimurium). The morphological changes in B. subtilis and S. typhimurium were also evaluated by FE-SEM analysis, which showed that some cells were partially damaged and distorted in shape upon treatment with NiO NPs, thus demonstrating their promising antibacterial activities.